(3CLhHI dYTQ eSGFds - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GdMeO ddg Gdehab hGdedge hGdeSOO gPg CLhHI Yf YTQ eSGFd SFdfG YfgG s
(3BNQgG (B:s
(3hGdeJYGdL GHJOGDg ef GdHOf , aGdaYd ef GdaGYd ai GdYGed dGLd GdZGjI dJMUjd GdUhQI s
(3Vef eLehY , JQJjHgG (B: 4s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs